A QUALITATIVE STUDY ON GAMERS’ PERCEPTION AND INTENTION TOWARDS ESPORTS PARTICIPATION - Loh How Zheng; Seow Ai Na; Chang Jing Jing (International Journal of Accounting, Finance and Business, 2023)
eSports or electronic sports is a competitive video game activity. It involved a group of gamer or teams rival with each other for winning the match. Despite eSports segment has contributed lots of paybacks to the world, however, there are still a little known about how the general public think about it. In particular, how eSports can trigger the gamers to participate in eSports. Hence, the purpose of carry out this qualitative research is to understand gamers’ perception towards eSports in Malaysia. A semi-structural interview was applied, with total of 5 student-gamers from the gaming club of private university were invited. Thematic analysis was used to analysed the collected responses. Findings suggested that gamers are motivated mainly by the positive factors include social interaction, enjoyment, stress relief and knowledge improvement. Participants also mentioned that gaming addiction served as one of critical factor towards eSports participation intention. The results from this study are able to provide useful knowledge and guidance to the policy makers, future scholars, eSports marketers, and other relevant parties.